Cellular and molecular determinants of stroke-induced changes in subventricular zone cell migration. - Young, C; Brooks, K; Buchan, A; Szele, F (2011)
A remarkable aspect of adult neurogenesis is that the tight regulation of subventricular zone (SVZ) neuroblast migration is altered after ischemic stroke and newborn neurons emigrate towards the injury. This phenomenon is an essential component of endogenous repair and also serves to illuminate normal mechanisms and rules that govern SVZ migration. Stroke causes inflammation that leads to cytokine and chemokine release, and SVZ neuroblasts that express their receptors are recruited. Metalloproteinases create pathways and new blood vessels provide a scaffold to facilitate neuroblast migration between the SVZ and the infarct. Most experiments have studied the peri-lesion parenchyma and relatively little is known about SVZ remodeling after stroke. Migration in the SVZ is tightly regulated by cellular interactions and molecular signaling; how are these altered after stroke to allow emigration? Do ependymal cells contribute to this process, given their reported neurogenic potential? How does stroke affect ependymal cell regulation of cerebrospinal fluid flow? Given the heterogeneity of SVZ progenitors, do all types of neuroblasts migrate out, or is this confined to specific subtypes of cells? We discuss these and other questions in our review and propose experiments to address them.